Portrait of t Democracy Practice and the Identity (Ethnic) Politics Struggle in the Local Political Arena: A Sociology and History Review - Irwan Irwan; Zusmelia Zusmelia; Felia Siska (Jurnal Mamangan, 2022)
The period of social, economic and political transition is closely related to the collapse of the Suharto regime and the reformtion. This condition is signed  by various kinds of conflicts , starting in the national and local political arena. Political propaganda  at that time occured when  the country was still in the authoritarian and centralistic spirit of the Suharto government. In fact, local actors and national politics are moving the issue to take power. This study focuses on the analysis of Indonesia  democratic struggles in the dynamics of identity politics, the practice of identity politics during the New Order era was given the  space in carrying out the  movements and compared to the reformation period in Riau Province and the process of strengthening identity politics in the local sphere in Riau Province. This study used literature study in analyzing with sociological and historical theory. The results of this study showed  that identity politics in Riau Province during the New Order and Reformation eras was different. During the New Order era, identity politics had no space and local people were shifted or removed, while during the reformation period, identity politics was open and expanded the contents of local people to become leader so it emerges the  conflicts and presenting cases at the local level. This study brings out  the term symbolic power in the local democratic process and carries the value of the  nationalism spirit  in local communities